2022
DOI: 10.1124/jpet.122.001301
|View full text |Cite
|
Sign up to set email alerts
|

Cinnabarinic Acid Provides Hepatoprotection Against Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a chronic condition in which excess lipids accumulate in the liver and can lead to a range of progressive liver disorders including non-alcoholic steatohepatitis, liver cirrhosis, and hepatocellular carcinoma. While lifestyle and diet modifications have proven to be effective as NAFLD treatments, they are not sustainable in long-term and currently no pharmacological therapies are approved to treat NAFLD. Our previous studies demonstrated that cinnabarinic acid (CA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Joshi et al, in a series of papers, analyzed the cytoprotective effects of CA against apoptosis induced by endoplasmic reticulum stress, oxidative stress, and alcohol insult (acute and chronic) and in non-alcoholic fatty liver disease [ 86 , 87 , 95 , 97 ]. They revealed that the CA-driven cytoprotecting activity is associated with the activation of AhR.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Joshi et al, in a series of papers, analyzed the cytoprotective effects of CA against apoptosis induced by endoplasmic reticulum stress, oxidative stress, and alcohol insult (acute and chronic) and in non-alcoholic fatty liver disease [ 86 , 87 , 95 , 97 ]. They revealed that the CA-driven cytoprotecting activity is associated with the activation of AhR.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…CA treatment significantly lowered body mass gain and decreased hepatic steatosis both before and after the established NAFLD. CA decreased free fatty acid uptake by downregulation of Cd36 expression as well as attenuated lipogenesis [ 97 ]. CA- induced AhR was unable to interact with the Cyp1a1 promoter and therefore did not increase its expression in isolated primary hepatocytes or in vivo [ 1 , 98 ].…”
Section: However Ahr Signaling Also Attenuates Nafldmentioning
confidence: 99%
“…These epigenetic modifications, which were observed in response to CA but not upon TCDD treatment, have been known to decrease DNA-histone interactions, open the chromatin structure and lead to the AhR-mediated transcription activation of Stc2 without Cyp1a1 induction [ 101 ]. The CA-induced AhR-mediated Stc2 induction is thus protective against steatosis, inflammation and liver injury observed in NAFLD [ 97 ]. (4) AhR signaling is also known to cross react with other signaling pathways involved in lipogenesis and oxidative metabolism.…”
Section: The Yin–yang Of Ahr Protection Against Nafld—a Conundrum!mentioning
confidence: 99%
“…CA also has cytoprotection against steatosis and hepatic damage in an Stc2-dependent manner in alcoholic liver disease mouse models by modulating ERK1/2 activity. Overall, these studies underline the existence of a CA-AHR-STC2 signaling cascade relevant in those liver diseases [ 69 ].…”
Section: Sessions and Presentationsmentioning
confidence: 99%